A novel HLA allele, HLA‐A*32:74, detected by sequencing in a Chinese individual. (17th August 2021) - Li, Xiao‐Feng; Liu, Ying; Zhang, Xu; Lin, Feng‐Qiu; Li, Jian‐Ping
Abstract : HLA‐A*32:74 has one nucleotide change from HLA‐A*32:01:01:01 where alanine (211) is changed to glutamate.